QUALIDADE DE GAMETAS COM A TÉCNICA DE ENDOSCOPIA EM CURIMBA (Prochilodus lineatus) - Andrade, Estefânia de Souza; Ferreira, Mônica Rodrigues; Paula, Daniella Aparecida de Jesus; Murgas, Luis David Solis; Felizardo, Viviane de Oliveira; Veras, Galileu Crovatto (Archives of Veterinary Science, 2012)